Meta-Analysis of Sex Differences in Social and Communication Function in Children With Autism Spectrum Disorder and Attention-Deficit/Hyperactivity Disorder - Mahendiran, Tania; Brian, Jessica; Dupuis, Annie; Muhe, Nadia; Wong, Pui-Ying; Iaboni, Alana; Anagnostou, Evdokia (Frontiers in Psychiatry, 2019)
Background: Sex differences in the prevalence of neurodevelopmental disorders such as autism (ASD), attention-deficit hyperactivity disorder (ADHD), and obsessive-compulsive disorder (OCD), have been well documented; still studies examining sex differences in social and communication in these disorders remain limited and inconclusive. Methods: Using PRISMA guidelines, a search was performed on studies (2000-2017) examining sex differences in social and communication abilities in ASD, ADHD and OCD compared to controls. Results: Eleven studies met criteria for ASD, 6 studies for ADHD and none met criteria for OCD. No significant sex differences were found between ASD and controls in social (p=0.5), or communication abilities (p=0.5) and between ADHD and controls in social abilities (p=0.7). No studies were identified to evaluate sex differences in communication in ADHD. Significant heterogeneity was noted in all analyses. Type of measure may have partially accounted for some variability between studies. Conclusions: A limited number of studies did not detect sex differences in social and communication abilities in children with ASD and ADHD; however significant heterogeneity was noted. Future larger studies, controlling for type of measure and including adequate numbers of female participants are required to further understand sex differences in these domains.